Appreciating the shades of gray: a case for Computer-Aided Nodule Assessment and Risk Yield (CANARY)-based risk stratification of lung adenocarcinomas - Maldonado, Fabien; Peikert, Tobias; Bartholmai, Brian J.; Rajagopalan, Srinivasan; Karwoski, Ronald A. (Journal of Thoracic Disease, 2016)
We read with great interest the invited commentary by Drs. Wilson and Pu on our computed tomography (CT)-based quantitative imaging tool for the non-invasive risk stratification of lung adenocarcinomas: Computer-Aided Nodule Assessment and Risk Yield (CANARY) (1). While we are pleased to see the discussion on the scope and relevance of our research, we would like to use this opportunity to respond to the points made by our colleagues and attempt to clarify any misunderstanding about CANARY.